Comparison of peak lumbar lordosis between some basic movements of rhythmic gymnastics - Eyssartier, C.; Billard, P.; Robert, M.; Thoreux, P.; Sauret, C. (ISBS Proceedings Archive (Michigan), 2022)
To assist coaches in managing gymnasts, a good knowledge of the movements most likely to cause back pain is required. In rhythmic gymnastics (RG), this can be considered as identifying movements involving very high lumbar curvatures. To quantify the lumbar lordosis during some basic RG movements (ring, penché, penché with rotation, split leap, turning split leap, and front and back walkovers), eight gymnasts were enrolled and a 3D motion analysis was performed based on motion capture data, a musculoskeletal model and low-dose biplanar radiographs for model personalisation purposes. The ring and both the front and back walkovers were the movements studied involving the lumbar spine in extension the most but also resulting in the highest dispersion between gymnasts. Hence, future works should investigate the causes of this greater dispersion.